Enhancement of Polyphenol Bio-Accessibility from Maqui Residue Through Ultrasound-Assisted O/W Nano-Emulsions Stabilized with Oat Protein and Sodium Alginate - Rivera-Tobar, D (Elsevier Ltd, 2025)
This study aimed to enhance the bio-accessibility of polyphenols extracted from maqui (Aristotelia chilensis) residue through the development of ultrasound-assisted oil-in-water (O/W) nano-emulsions stabilized by oat protein and sodium alginate. A 32 factorial design was employed to investigate the influence of protein concentration (8 %, 10 %, 12 %) and ultrasonic power (200, 400, 600 W) on physicochemical properties, encapsulation efficiency, storage stability, and in vitro release. The optimized formulation (8 % protein, 600 W) exhibited the smallest particle size (353.4 nm), a zeta potential of −26.2 mV, and the highest encapsulation efficiency (96.2 %). However, the formulation with 8 % protein and 400 W showed superior stability and polyphenol release during simulated intestinal digestion (>50 %). Unlike previous studies using conventional proteins or synthetic surfactants, this work demonstrates the effective use of plant-based biopolymers (oat protein and alginate) in ultrasound-assisted nano-emulsions to valorize agro-industrial residue. The approach offers a sustainable strategy for improving the delivery and intestinal bio-accessibility of polyphenols, with potential applications in functional foods and nutraceuticals. © 2025 Elsevier Ltd
Keywords: Ultrasound; Nano-emulsions; Maqui; Sodium alginate; Oats protein; Bio-accessibility